KEBIASAAN MEMBERIKAN MAKANAN KEPADA BAYI BARU LAHIR DI PROPINSI JAWA TENGAH DAN JAWA BARAT (NEW BORN INFANT FEEDING HABIT IN CENTRAL JAVA AND WEST JAVA) - Widodo, Yekti (Media Penelitian dan Pengembangan Kesehatan, 2001)
Initiation of breast milk should be given to the baby as soon as possible, not more than half hour after the baby was bora If initiate of breast milk is not early, it will be difficult to avoid introduced other food than breast milk to new bom be infant. The objective of research is to know how the community habit, especially in Central Java and West Java in order with infant feeding for new born infant The result of the research showed 77,0% respondent introduced other food to new born infant and 23% respondents initiated breast milk soon after the baby bora Two reason for mother introduced other food before they give breast milk First, as "baby food' for the new born infant (knowing as prelacteal food). Kind of this food are honey (64,2%), water-honey (11,73%), boiled water (13,5%), and milk formula (10,6%). They gave this food for prelacteal food, because breast milk not flows yet (64,8%), for the baby not hungry (14,8%), suggested by traditional birth attendance (dukun bayi), suggested by grandmother (4,7%) and mother not ready yet to give breast milk (3,6%). Second, Not as 'baby food', but because the culture. Usually they give other food just once time, in the first minutes of the baby life. After that, they give breast milk. The kinds of this food are solution water coffee (19,4%), pepper (29,6%), "kurma" (3,7%), onion (21,3%), lime juice (5,6%) and salt solution (18,8%), also white egg (1,9%). The reason to give that food are: to bring out dirty things from baby stomach (82,4%) as the not cramp (13,9%), and religion (3,7%). Actually, the first reason suggested by traditional birth attendance as a "helping delivery package" . This always doing by the traditional birth attendance